Leaves calorific values of selected species in burnt tropical peat swamp forest in Selangor, Malaysia - Ulok, Gerald; Nuruddin, Ahmad Ainuddin; Go, Rusea; Md Tahir, Paridah (Science Publications, 2016)
Forest fire in Malaysia’s peat swamp forest is a major concern since it is contributing to the country’s haze episode. Forest fire in peat areas is difficult to be extinguished and may occur for days. Understanding fuel characteristics is the key to develop effective fuel management in peat swamp forest. The objectives of this study were to evaluate the common species coverage and calorific value of the common plants species in the burnt peat swamp forest. The study was conducted in the rehabilitated areas of Raja Musa Forest Reserved, Selangor, Malaysia. 9 plots were established along canal 6 in Compartment 100 of the Raja Musa Forest Reserved. Plants were surveyed in the 9 plots and based on the survey, 8 species (Imperata cylindrica, Macaranga pruinosa, Nephrolepis biserrata, Melastoma malabathricum, Lygodium flexuosum, Uncaria tomentosa, Scleria sumatrensis and Melicope latifolia) most higest coverage found in that area. Scleria sumatrensis had the highest coverage of 40% followed by Melastoma malabathricum of coverage of 21%. The data suggested that the 8 species covered most of the study area and have the potential to be forest fuel. Uncaria Tomentosa had the highest calorific value with 4832.8 cal/g while Nephrolepis biserrata had the lowest value of 3825.2 cal/g. The findings concluded that the Sceleria sumatrensis had the highest coverage and calorific values of the selected plants vary with species. These information provide insight on the species common in burnt tropical peat swamp forest and are helpful in formulating forest fire control programme.